Investigating Workplace Music Preferences and Their Role in Employee Productivity and Well-Being: A Cross-Sectional Study in Indonesia - Zandra, Rully Aprilia; Jamnongsarn, Surasak; Ismail, Adzrool Idzwan bin; Setiyowati, Arbin Janu; Hidayatullah, Hengki Tri (Harmonia: Journal of Arts Research and Education, 2025)
Music is conventionally perceived as a medium of entertainment and artistic expression. However, among employees, music assumes a broader functional role, supporting productivity and psychological well-being across diverse workplace contexts. This study aimed to investigate the functional role of music among employees experiencing work-related stress and low motivation. A cross-sectional study was administered to 500 employees representing various socioeconomic and educational backgrounds. Participants reported their musical preferences and the perceived psychological impacts of music during different emotional states at work. Data analysis, including word cloud visualization and heatmap modeling, revealed that genres such as Pop and Dangdut dominated across both emotional conditions. However, the functional objectives of music usage differed; employees experiencing stress favored music for emotional balance and familiar comfort, while those facing low motivation preferred music that energized and re-engaged cognitive resources. The findings highlight that music serves adaptive emotional and cognitive regulatory functions, leading to increased productivity, emotional stabilization, and sustained concentration. These results offer practical implications for workplace well-being strategies, emphasizing the potential of personalized auditory environments in enhancing employee resilience and performance.